Experiences of nurses regarding challenges faced while dealing with psychiatric patients in both public and private tertiary care hospitals of Karachi, Pakistan - Daizi Jafar,; Alia Nasir,; Amber Hussain, (Journal of the Pakistan Medical Association, 2023)
Objective: To explore the challenges of mental health nurses in dealing with psychiatric patients. Method: The qualitative, descriptive, phenomenological study was conducted at three public and private psychiatric setups in Karachi from August 13 to October 30, 2018, and comprised mental health nurses having a minimum 6-month experience of working in a psychiatric ward. Data was collected using focus group discussion using a semi-structured interview guide. The proceedings were transcribed, translated and analysed using thematic analysis, leading to the formation of themes, categories and sub-categories. Result: Of the 15 nurses with mean age 25±1.95 years, 5(33.3%) were from the public sector and 10(66.6%) were associated with private-sector institutions. Besides, 7(46.6%) nurses had work experience up to 5 years. There were three sessions of focus group discussion; 1(33.3%) of public-sector nurses and 2(66.6%) of priver-sector nurses. Each session had 5(33.3%) participants. Post-transcription feedback was provided by 8(53%) nurses. There were 4 themes; lack of resources, safety-related challenges, lack of staff capacity building, and lack of support. The themes overall had 14 categories and 7 sub-categories. Conclusion: The nurses exposed to patient aggression should be provided debriefing sessions to deal with possible burnout. Key Words: Career, Mental health nurses, Mental health, Public health, Stigmatised, Violence.